Development of a multi-rotor VTOL UAV : numerical study of rotor-wake induced interference drag on a VTOL UAV - Lim, Jarad Jian An (2018)
Momentum Actuator (MA) models in CFD are analysed for their practical and accurate representation of aircraft propulsion. Methods for determining the inputs to these MA models are validated, and the MA model is used on a half-body Electric Vertical Take-Off and Landing (eVTOL) aircraft. The effect of rotor wake on aerodynamic drag in cruise flight and longitudinal forces in hover flight is numerically evaluated, and recommendations are made towards optimising the design of the aircraft.